2004
DOI: 10.1007/s00415-004-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin in post-stroke patients: stiffness modifications and clinical implications

Abstract: BT can be considered a valid therapeutic tool in all spastic patients, because of immediate advantages: reduction of muscle hypertonia, pain relief, improvement in selected motor performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
1
21
0
5
Order By: Relevance
“…121,127 ). An influence on intrafusal fibre function of this toxin was discussed 128,129 . Nevertheless, there are also reports indicating, that intrathecal baclofen can reduce hyperactive reflexes without producing significant weakness [130][131][132] .…”
Section: Therapeutical Consequencesmentioning
confidence: 99%
“…121,127 ). An influence on intrafusal fibre function of this toxin was discussed 128,129 . Nevertheless, there are also reports indicating, that intrathecal baclofen can reduce hyperactive reflexes without producing significant weakness [130][131][132] .…”
Section: Therapeutical Consequencesmentioning
confidence: 99%
“…30 The concern that botulinum toxin may cause significant weakening of muscles and therefore reduced function seems not to occur, with some authors reporting increased strength. 34 A recent European consensus statement on the use of botulinum toxin in adult spasticity provides the necessary advice about indication and treatment.…”
Section: Spasticitymentioning
confidence: 98%
“…[2][3][4][5][6][7]9,[11][12][13][14][15] Of the reviewed studies, results showed statistical significance of improving spasticity in the muscles injected with BTX-A.…”
Section: Spasticity Scalesmentioning
confidence: 99%